Identifikasi Faktor Pemilihan Penyedia Jasa Foto Katalog Produk (Studi pada Pengusaha Online Shop) - Dyah Astuti, Widya Ayu; Sanaji, Sanaji (Jurnal Ilmu Manajemen, 2021)
This study aims to identify the factors considered by online shop owners in choosing photo catalogue services. This research is quantitative type. This study's data sources are primary data conducted by distributing questionnaires to research respondents. This research sample is 54 online shop owners who use product catalogue photo services. This research's variables are product attributes consisting of the brand, quality, features, design, price, and guarantee. The data collection technique uses questionnaires to 54 samples of product catalogue service users. In this case, the weighting questionnaire was filled in, done with Osgood's semantic differential measurement scale. This study's data analysis techniques were factor analysis, factor feasibility test, and correlation analysis. Are six factors to consider online businesspeople using product catalogue photo services. Product quality factors include high photo resolution, proper photo brightness; the resulting photo focuses on the product and colour match. The Feature Factor includes distinctive features, exceptional light-dark levels, and distinctive themes. Design factors include photo clarity, photo editing, and ready-to-upload photos. Factors include price according to quality, affordable prices, discounted prices, and price variations. The warranty factor includes product warranty items, a money-back guarantee, and a photo re-guarantee. Promotional factors that are informative, attractive promotions, promotions that are easy to remember, service readiness, problem-solving, services that are as promised and responsive to complaints